Biodegradable nanocellulose reinforced biocomposites for food packaging – a narrative review and future perspective - Sadhana Jadaun; Usha Sharma; Ringshangphi Khapudang; Saleem Siddiqui (Journal of Water and Environmental Nanotechnology)
Conventional food packaging materials such as plastic or other petro-based polymers provide the necessary strength and barrier qualities, but they are associated with economic and environmental associated hazards. In order to have a material that can effectively compete with petroleum-based plastics, the ecofriendly biodegradable biopolymer reinforced bio-nanocomposites from renewable agricultural biomass can be a promising alternative. Lignocellulosic biomass from agricultural wastes can serve as promising raw material for nanocellulose extraction. This review focuses on extensive studies done on pretreatment, isolation of nanocellulose along with their role as reinforcement agent in various biopolymers such as poly-lactic acid, starch, chitosan, alginate and carrageenan. The uniqueness of this review is to give readers a thorough overview of the impact of nanocellulose on the mechanical, barrier, and thermal properties of biopolymeric film. The review will also provide a comprehensive understanding of the supply chain’s elements, their opportunity and constraints for shifting the sustainable production system of cellulose nanocomposites towards circular economy. Efforts have also been made to combine all the recent studies related to key aspects and engineering of nanocellulose biocomposites. The concept of 3D/4D printing technology of cellulose nanocomposites in conjunction with Shape Memory Polymers (SMP) in the domain of commercial development of smart materials and self- folded packages for food applications has also been discussed.